Modeling the impacts of petrophysical and textural parameters on dissolution of carbonate rocks at 25°C, 50°C, and 75°C - Ben-Awuah, Joel; Padmanabhan, E.; Andriamihaja, S.; Sokkalingam, R. (Slovnaft VÚRUP, 2016)
Carbonate rocks react easily with the surrounding environment, especially in acidic environment. This property leads to very complex and heterogeneous fabric but can also be an important advantage in EOR method and CO2 sequestration. Extensive studies have been carried on carbonate dissolution but the dissolution response of different microfacies at different temperature is still unpredictable and challenging to predict. The aim of this study is to develop predictive dissolution models for different carbonate microfacies at 25°C, 50°C and 75°C, under controlled conditions. The models are developed as a function of time of dissolution, pore-filling carbonate crystal size, porosity and permeability. The results show that as a function of only time, the dissolution models are described by log linear function where the dissolution rate increases as the temperature increases. The other developed dissolution models show that time and porosity have positive impact on dissolution whereas crystal size slows the dissolution. Based on the models, permeability appears to have no impact on dissolution. The predicted results obtained from the different models are in good agreement with the measured experimental data.